Reviving the China-Islamic World Connection: from Historical Trade to the Belt and Road Initiative and Beyond - Boon Dar Ku; Mohamad Ainuddin Iskandar Lee (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: This paper presents analysis of the relationship between China and the Islamic world, focusing on economic, political and cultural dimensions. Drawing on literature review and secondary data analysis, including academic studies and reports from international organisations, the study investigates historical interactions between China and Islamic civilisations, highlighting trade as the key driver of their engagement. The findings demonstrate that historical China-Islamic world interactions were largely characterised by reciprocal exchange, in which Islamic commercial networks, knowledge systems and religious institutions played a formative role in shaping China’s external engagements. The paper further examines the contemporary relationship, focusing on the Belt and Road Initiative (BRI) as the most significant economic framework connecting the two regions. The study finds that in the contemporary period, the relationship has evolved into an asymmetrical form of engagement, with China exercising greater economic leverage and strategic influence through infrastructure investment, energy cooperation and development financing. This shift reflects broader changes in the global political economy rather than a contradiction with earlier historical patterns. In addition, the study explores China’s approach to Islam in the context of Muslim minority governance, analysing challenges associated with the treatment of Uyghur Muslims in Xinjiang and their implications for China’s relations with the Muslim world. The findings indicate that domestic governance practices related to Islam have become a significant constraint on China’s soft power in Muslim-majority societies, shaping diplomatic perceptions despite deepening economic ties. The study adopts historical, political-economic and socio-religious perspectives to provide a concise and integrated understanding of the dynamics shaping contemporary China-Islamic world relations. Abstrak: Artikel ini menyajikan analisis mengenai hubungan antara Tiongkok dan dunia Islam dengan menyoroti dimensi ekonomi, politik, dan budaya. Dengan menggunakan kajian literatur dan analisis data sekunder, termasuk studi akademik serta laporan dari organisasi internasional, penelitian ini menelusuri interaksi historis antara Tiongkok dan peradaban Islam, dengan menempatkan perdagangan sebagai faktor utama yang mendorong hubungan tersebut. Temuan penelitian menunjukkan bahwa interaksi historis antara Tiongkok dan dunia Islam pada umumnya bersifat timbal balik, di mana jaringan perdagangan Islam, sistem pengetahuan, serta institusi keagamaan memainkan peran penting dalam membentuk hubungan eksternal Tiongkok. Tulisan ini juga mengkaji hubungan kontemporer antara keduanya, dengan menyoroti Belt and Road Initiative (BRI) sebagai kerangka ekonomi paling signifikan yang menghubungkan kedua kawasan. Hasil penelitian menunjukkan bahwa pada periode modern, hubungan tersebut berkembang menjadi lebih asimetris, dengan Tiongkok memiliki pengaruh ekonomi dan strategis yang lebih besar melalui investasi infrastruktur, kerja sama energi, dan pembiayaan pembangunan. Perubahan ini mencerminkan dinamika ekonomi-politik global yang lebih luas, bukan merupakan penyimpangan dari pola historis sebelumnya. Selain itu, penelitian ini juga mengeksplorasi pendekatan Tiongkok terhadap Islam dalam konteks pengelolaan minoritas Muslim, khususnya terkait perlakuan terhadap Muslim Uyghur di Xinjiang serta implikasinya terhadap hubungan Tiongkok dengan dunia Islam. Temuan menunjukkan bahwa praktik domestik dalam mengelola isu keagamaan menjadi salah satu faktor pembatas bagi soft power Tiongkok di negara-negara mayoritas Muslim, sekaligus memengaruhi persepsi diplomatik meskipun hubungan ekonomi terus menguat. Penelitian ini menggabungkan perspektif historis, ekonomi-politik, dan sosial-keagamaan untuk memberikan pemahaman yang ringkas namun komprehensif mengenai dinamika hubungan Tiongkok dan dunia Islam kontemporer.